Optimizing electronic structure through point defect engineering for enhanced electrocatalytic energy conversion - Wei Ma; Jiahao Yao; Fang Xie; Xinqi Wang; Hao Wan; Xiangjian Shen; Lili Zhang; Menggai Jiao; Zhen Zhou (Green Energy & Environment)
Point defect engineering endows catalysts with novel physical and chemical properties, elevating their electrocatalytic efficiency. The introduction of defects emerges as a promising strategy, effectively modifying the electronic structure of active sites. This optimization influences the adsorption energy of intermediates, thereby mitigating reaction energy barriers, altering paths, enhancing selectivity, and ultimately improving the catalytic efficiency of electrocatalysts. To elucidate the impact of defects on the electrocatalytic process, we comprehensively outline the roles of various point defects, their synthetic methodologies, and characterization techniques. Importantly, we consolidate insights into the relationship between point defects and catalytic activity for hydrogen/oxygen evolution and CO2/O2/N2 reduction reactions by integrating mechanisms from diverse reactions. This underscores the pivotal role of point defects in enhancing catalytic performance. At last, the principal challenges and prospects associated with point defects in current electrocatalysts are proposed, emphasizing their role in advancing the efficiency of electrochemical energy storage and conversion materials.